Elementary School Students' Science Learning Motivation through RADEC Model - Putri, Devi Septiani; Sopandi, Wahyu; Sujana, Atep; Pramswari, Lungguh Puri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to describe students’ learning motivation through the RADEC (Read, Answer, Discussion, Explain, and Create) Model on Air material for fifth-grade elementary school students. This descriptive qualitative research analysis involved 38 fifth-grade students in one of the Sumedang public elementary schools. The research instrument in the form of a science learning motivation scale questionnaire consists of 15 statements with 4 answer choices, namely Strongly Agree (SA), Agree (A), Disagree (D), and Strongly Disagree (SD) which is based on 7 indicators, namely (1) Persevering in facing tasks, (2) being tenacious in facing difficulties (not giving up quickly), (3) Shows interest in various kinds of problems for adults, (4) Prefers independent learning, (5) Can defend his opinion, (6) It is not easy to let go of things that have been believed, and (7) Happy to find and solve problems. The data obtained from the questionnaire were nalysed through tabulation of data using a formula to determine the percentage of student answers. The results showed that the indicators of student learning motivation with the RADEC Model criteria were interrelated. In addition, based on the results of the average score of the overall statement on the questionnaire, all indicators of student learning motivation are included in the very good criteria, namely 81.22%. So it can be concluded that with the application of the RADEC Model there is a high learning motivation in science learning in fifth-grade elementary school students in the Sumedang area.